Accidental ingestions to known allergens by food allergic children and adolescents. Issue 8 (22nd June 2021) - Hicks, Allison; Palmer, Claire; Bauer, Maureen; Venter, Carina
Abstract: Background: Accidental ingestions (AI) of food allergens in children compared with adolescents with food allergies are poorly characterized. It is suggested that AIs are higher in adolescents than children and that their reactions may be more severe, presumptively due, at least in part, to increased risk‐taking behavior. We compared reported AIs in children versus adolescents. Methods: An online cross‐sectional survey was distributed to parents of children with food allergies via Twitter, food allergy advocacy groups in the UK, South Africa, and Australia, and locally at Children's Hospital Colorado. Results: Of 558 respondents, 105 were parents of adolescents, and 453 had children <12 years. 73% (341) reported an AI since diagnosis, with 85% of adolescents having had an AI versus 70% of children ( p  = 0.0058). The annualized rate of AI was significantly lower in the adolescent population at 0.21 versus 0.53 in children ( p  = <0.0001). Although adolescents reported fewer severe reactions (2% vs. 16%, p  = 0.0283), more adolescents required epinephrine administered by a medical professional for their most severe AI, (48% vs. 24%, p  = 0.0378). Comparison of the two age groups is limited by the fact that many AIs in the adolescent group occurred prior to age 12. There was no significant difference between the groups as to where the food was consumed or the type of food. There was a significant difference in accidental ingestions in patients in all age groups with more than one reported food allergy; 78% of those with more than one food allergy reported a prior history of at least one accidental ingestion, compared with 59% in those with a single food allergy ( p  < 0.0001). Regional differences were also noted with respondents in the United States reporting 0.3 accidental ingestions a year, 0.4 in the UK, and 0.5 in other countries ( p  = 0.0455). The number of reactions was, on average, 27% lower (95% CI: 40, 11%) in the United States compared with the UK ( p  = 0.0019). Conclusion: The number of severe reactions, and epinephrine need, differs in children compared with adolescents, although many of the reported reactions in both groups occurred before the age of 12. There were also regional differences with the United States reporting a lower number of AIs and less AIs per year than the other participating regions, as well as increased rates of AI in participants with more than one food allergy. Further characterization of the differences in AIs between children and adolescents, as well as between regions, is needed to assist with more patient‐centered anticipatory guidance.